1983
DOI: 10.1126/science.6603018
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Immunosuppression: Inescapable But Not Escapable Shock Suppresses Lymphocyte Proliferation

Abstract: Rats were given series of escapable shocks, identical inescapable shocks, or no shock. The subjects were reexposed to a small amount of shock 24 hours later, after which an in vitro measure of the cellular immune response was examined. Lymphocyte proliferation in response to the mitogens phytohemagglutinin and concanavalin A was suppressed in the inescapable shock group but not in the escapable shock group. This suggests that the controllability of stressors is critical in modulating immune functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
1
4

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(116 citation statements)
references
References 26 publications
3
106
1
4
Order By: Relevance
“…While such effects have been demonstrated in a number of animal studies (Monjan, 1981;Laudenslager et al, 1983), the human literature is more limited (Bartrop et al, 1977;Palmbald, 1981;Jemmott et al, 1983). In earlier studies, we found that medical students had significantly poorer natural killer-cell (NK) activity in blood samples obtained during examinations, in contrast to baseline samples drawn 1 month previously (Kiecolt-Glaser et al, 1984a).…”
Section: Introductionmentioning
confidence: 76%
“…While such effects have been demonstrated in a number of animal studies (Monjan, 1981;Laudenslager et al, 1983), the human literature is more limited (Bartrop et al, 1977;Palmbald, 1981;Jemmott et al, 1983). In earlier studies, we found that medical students had significantly poorer natural killer-cell (NK) activity in blood samples obtained during examinations, in contrast to baseline samples drawn 1 month previously (Kiecolt-Glaser et al, 1984a).…”
Section: Introductionmentioning
confidence: 76%
“…Kamen-Siegel, Rodin, Seligman, & Dwyer, 1991;Laudenslager, Ryan, Drugan, Hyson, & Maier, 1983;Sieber et al, 1992). Rodin and Langer (1977) found that instilling a sense of control in institutionalized older people reduced subsequent mortality, and Schulz (1976) found that institutionalized older people who were visited by student volunteers on a predictable or controllable schedule were judged happier and healthier than no-visit controls.…”
Section: Discussionmentioning
confidence: 99%
“…Control, or the perception of control, over a stressor also has a big part on the physiological effect. Allowing rodents to escape or control when a negative stressor, such as an electric shock, ends increases tumor rejection, reduces tumor growth and increases lymphocyte stimulation 51,52 . Furthermore, even the perception of control is sufficient to elicit the same psychophysiological buffering to a stressor as actual control 53 .…”
Section: Thermal Stress and Its Effect On Mouse Modelsmentioning
confidence: 99%